The Implementation of Cognitively Challenging Tasks: The Role of Science Teachers' Professional Development and Teaching Experience - Palmira Pečiuliauskienė; Lina Kaminskienė (MDPI AG, 2022)
This study deals with the implementation of cognitively challenging tasks for students in science education following professional development interventions for teachers based on the theory of change. These tasks require non-routine behaviors and encourage students to work beyond instructions and accept a high level of responsibility. This study explores how the content of professional development, the duration of professional development, and the extent of the teaching experience of science teachers are associated with the implementation of cognitively challenging science tasks in science education. A secondary data analysis of Trends in International Mathematics and Science Study (TIMSS) 2019 data from three countries (Singapore, Lithuania, and South Africa) was conducted. Ordinal logistic regression (OLR) was used to predict an ordinal dependent variable (the implementation of cognitively challenging science tasks) according to the independent variables (the content of professional development, the duration of professional development, and the extent of the teaching experience of science teachers). The results of the OLR confirmed that the implementation of cognitively challenging tasks is associated with professional development content (improving students' critical thinking or inquiry skills and science content) and the extent of the teaching experience of science teachers from the selected countries.